2016
DOI: 10.2147/oajsm.s93047
|View full text |Cite
|
Sign up to set email alerts
|

What is the most effective posture to conduct vibration from the lower to the upper extremities during whole-body vibration exercise?

Abstract: BackgroundWhole-body vibration (WBV) exercise is widely used for training and rehabilitation. However, the optimal posture for training both the upper and lower extremities simultaneously remains to be established.ObjectivesThe objective of this study was to search for an effective posture to conduct vibration from the lower to the upper extremities while performing WBV exercises without any adverse effects.MethodsTwelve healthy volunteers (age: 22–34 years) were enrolled in the study. To measure the magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In conclusion, the current study showed that static squat position with different muscle length of plantar-flexors during 26 Hz WBV did not affect jumping heights compared with the no-WBV condition. Practically, lower frequencies (20-30 Hz) (Cardinale & Lim, 2003), 90º squat position (Avelar et al, 2013;Tsukahara et al, 2016) with heels raised (Di Giminiani et al, 2013) maximizes muscle activity and vibration effect, but squat position with or without heels raised has no effect on jump performance. Besides that WBV affects acute jump performance regardless of short or long muscle length during WBV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the current study showed that static squat position with different muscle length of plantar-flexors during 26 Hz WBV did not affect jumping heights compared with the no-WBV condition. Practically, lower frequencies (20-30 Hz) (Cardinale & Lim, 2003), 90º squat position (Avelar et al, 2013;Tsukahara et al, 2016) with heels raised (Di Giminiani et al, 2013) maximizes muscle activity and vibration effect, but squat position with or without heels raised has no effect on jump performance. Besides that WBV affects acute jump performance regardless of short or long muscle length during WBV.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies focused on body position during WBV. According to these studies, knee flexion of 90º during WBV is associated with a greater magnitude of vibration to the calf compared to the knee flexion of 30º, and 90 º squat position may be useful for conducting vibration to the calf (Tsukahara et al, 2016). Abercromby et al (2007) indicated that static squat position caused higher meuromuscular responses compared to dynamic squatting.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that WBV achieves positive effects on the neuromuscular system, such as strength, EMG signal, muscle activation, performance, induces increased blood concentrations of testosterone and growth hormone, improves muscle dynamics, muscle activation, dynamic joint stability, coordination and proprioception, muscle fatigue and joint mobility (4,11,16,19,20,(38)(39)(40)(41)(42). Due to these benefits, this technology has been tested in different audiences, such as athletes, in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention protocols were varied, however, most publications coincide with good results when using 30 Hz Acute Effects of WBV on Muscle Strength in Subjects with Shoulder Instability of frequency, a single session (acute effects), 3 series of stimulation, using the isometric arm flexion position with the hands on the platform. A single session of WBV application has shown positive results on the neuromuscular system and has been used as a protocol in several studies (5,(13)(14)(15)(16)(17)(18)(19)(20). Within the WBV studies, there are also those who investigated the effects of this technology on joint instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary effects were not considered for the lab-based testing interventions because of a focus on the primarily vibration-related neuromuscular effects. The transmission of vibrations also depends on arm or body posture (38,39). An unintentional optimization of the seating position, such as changing the trunk posture to minimize the transmission of vibrations, can also influence muscular activation.…”
Section: Discussionmentioning
confidence: 99%